A utilização do direito de arena nos esportes eletrônicos - Romero, Ana Cristina Mizutori (2023)
Technological progress influences all areas of human life, including leisure, recreation and work. In this sense, sport was also impacted by advances in technology, which led to the emergence of the so-called eSports. The present study has the objective of determining the right of arena related to the electronic modality of sports in Brazil. To this end, bibliographic research was used through scientific articles, theses, dissertations, books, monographs and draft laws relevant to the theme. Finally, it was concluded that state intervention is extremely necessary in order to regulate the subject in a specific way, since, currently, what exists is the selfregulation of the market, capable of curtailing rights